Immobilization of amylase using chitosan beads as support - Almeida, Carlos M. S.; Nascimento de Jesus, Jean; Ferreira, Renata D. M.; Varandas, Vinícius S.; Cavalcante, Paula A. W.; Coêlho, Diego F.; Rodrigues, Jacqueline R. da S.; Souza, Roberto Rodrigues de; Oliveira, Thaynah S. de (Scientia Plena, 2017)
Amylases are hydrolases that are prominent, compared to other enzymes, accounting for 65% of the world’s market. They can be applied to any processes that require partial or complete hydrolysis of starch, such as: glucose production, the paper industry, brewing industry, food industry, among others. The use of enzymes in the industry brings great advantages, such as: a lower energy consumption; selectivity for the substrate; high activity and, in most cases, low production cost. However, it is still a costly catalytic route option, and it is necessary to use immobilization processes so that no further costs are generated in its recovery after the reaction. This work aimed to produce chitosan beads for use in the immobilization of amylase from a non-purified source. The enzymatic broth volume evaluated was 7 and 10 mL, with the highest rate of immobilization (36.04%) and recovered activity (12.36%) achieved using 7 mL of enzymatic broth. In the evaluation of the number of spheres used for immobilization, 6, 10 and 14 units were evaluated. It was found that the smallest number of spheres was sufficient to immobilize 54.71% of the enzymes. However, the recovery activity was the lowest (6.77%). Immobilization by covalent bonding presented better immobilization result compared to other immobilizations (54.71%), despite the lower result for recovery of activity (6.77%).